PMC physics. (BioMed Central, 2007)
"PMC Physics A is an international, peer-reviewed, open access journal that publishes articles on high-energy & nuclear physics, cosmology, gravity & astroparticle physics and also the instrumentation & data analysis of results in these areas"--Aims & scope (publisher's Web site, viewed Oct. 3, 2007).